Menakar Keadilan Sistem Pengupahan Go-Jek: Bukti Empiris dari Yogyakarta. - Syaparuddin Razak; Sari Utami (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This study aims to evaluate the wage system fairness of GO-JEK, namely whether the policies and strategies of GO-JEK's profit distribution have corresponded with the economic, religious and cultural standards in the operational area of ​​Yogyakarta, and using the Index of Fairness of Wage System (I-FWS) to measure that. The evaluation results showed that the wage system fairness of GO-JEK in the operational area of Yogyakarta both partially and simultaneously were in the category of “fair”. It means that all drivers got the same opportunity and equal and transparent treatment without any discrimination from PT. GO-JEK Indonesia in the operational area of Yogyakarta in obtaining a profit sharing as the partners of GO-JEK from the partnership business it operates.